A cadeia produtiva da pesca artesanal da vila de Japerica, São João de Pirabas, Pará, Brasil - GOMES, João Augusto Severino (2022)
The fishing activity is one of the jobs of great importance for humanity, because it is a nutritional source for billions of people, generating jobs for self-employed or contracted workers, reducing social inequalities and moving the economy of several countries. Given the complexity of the fishing activity, an important tool for analyzing this market is the analysis of the production chain, which makes it possible to evaluate the behavior between organizations (political and private), strategic business issues, technologies used, new arrangements and identify issues such as performance improvement and competitiveness. The present work aims to describe the artisanal fishing developed by fishermen from the Japerica district of the municipality of São João de Pirabas, taking into account the socioeconomic situation of the fishermen. The technical structure and production of fisheries and the fisheries production chain. Data for the study were obtained through a questionnaire with 45 fishermen residing in the study area. Information about the production chain and the commercialization of fish at the São João de Pirabas municipal fair is provided by fish brokers. Through this study, it was found that the fishermen are mostly adults and elderly, with incomplete elementary education, minimum wage as a monthly family income, with no other source of income, fishermen because there is no possibility of other occupations. Among them, gillnets are the most used fishing tools, and tails are the main fishing transport tools. Fish production is quite varied, and the fishing production chain is composed of artisanal fishermen, middlemen and consumers. The middleman is responsible for selling at the city fair. It is proposed as improvements to the fishing sector: the intensive action of Organs competent bodies to minimize predatory fishing in the region and educational measures, the implementation of the fishermen's cooperative to add value to the product of the fishing activity and the facilitated access to credit lines for funding and financing for the acquisition of fishing materials.